TRANSFORMASI KLASIBER MEMANFAATKAN DESAIN WEB RESPONSIF - Andhika Giri Persada (Faculty of Industrial Technology Universitas Islam Indonesia, 2015)
In recent years, students prefer to use mobile devices more frequently than desktop, when accessing information. Klasiber is a name of e-learning used in Islamic University of Indonesia (UII). So far, to access Klasiber, students on UII prefer to use desktop. Indeed, information architecture of Klasiber is designed only to accomodate desktop users. Questions of the research that appears from these problems are: How Klasiber be transformed so it can be accessed optimally using mobile devices. Second question is: How Klasiber adopts the responsive web design (RWD) to accommodate the variety of devices. In this paper, we developed prototypes of the new Klasiber based on RWD. Prototypes are developed as comparison with the previous Klasiber. Effectiveness of prototypes being developed is tested by using usability testing. The usability testing is designed based on Norman's emotional framework.